An outbreak of fluoroquinolone-resistant Pseudomonas aeruginosa ST357 harboring the exoU gene. Issue 8 (August 2018) - Kainuma, Atsushi; Momiyama, Kyoko; Kimura, Takeshi; Akiyama, Koichi; Inoue, Keita; Naito, Yoshifumi; Kinoshita, Mao; Shimizu, Masaru; Kato, Hideya; Shime, Nobuaki; Fujita, Naohisa; Sawa, Teiji
Abstract: Antimicrobial-resistant isolates of Pseudomonas aeruginosa collected from 2005 to 2014 in a university hospital in Kyoto, Japan, were retrospectively analyzed by multilocus sequence typing (MLST), exoenzyme genotype determination, integron characterization, and clinical associations. During the study, 1573 P. aeruginosa isolates were detected, and 41 of these were resistant to more than two classes of antimicrobial agents. Twenty-five (61.0%) isolates were collected from urine. All isolates were resistant to ciprofloxacin, 8 (19.5%) isolates showed resistance to imipenem/cilastatin, and 8 (19.5%) isolates showed resistance to meropenem. None of the isolates fulfilled the clinical criteria for multidrug-resistant P. aeruginosa . All isolates were negative in the metallo-β lactamase test. Thirty-six (87.8%) isolates were of the exoS ˗ exoU + genotype and 5 (12.2%) isolates were of the exoS + exoU ˗ genotype. Among 36 exoS ˗ exoU + isolates, 33 (80.5%) were ST357, and 3 (7.3%) were ST235. Five isolates of exoS + exoU ˗ were ST186, ST244, ST314, ST508, and ST512. Thirty-three isolates were positive for class 1 integrons and four different class 1 integrons were detected: aminoglycoside (2′) adenyltransferase and chloramphenicol transporter (AadB+CmlA6), OXA-4 β-lactamase and aminoglycoside 3′-adenyltransferase (OXA4+AadA2), AadB alone, and aminoglycoside acetyltransferase alone (AacA31). Among the 41 patients from which the isolates originated, the most common underlying disease was cancer in 16 patients (39%), and 9 patients (22.0%) died during the hospitalization period. There was no statistical correlation between MLST, exoenzyme genotype, and patient mortality. The results indicated outbreaks of fluoroquinolone-resistant P. aeruginosa in immunocompromised patients mainly due to the propagation of potentially virulent ST357 isolates possessing the exoU + genotype.